Policy for the Support of Creative Economy - Jozef Tvrdon; Eva Belvoncikova (European Regional Science Association (ERSA), 2012)
The newest theories of regional development accent an approach that the development of a region is influenced both by intraregional environment and but also by various institutes that create an environment, influence the creation of subjects relations and form communication rules for individual activities. Institutional surrounding and conditions in the region have an impact on successful regional development thereby directly influence its competitiveness. Presented paper is focused on evaluation of approaches to the supporting policy focused on a development of creative industries in regional context. The aim is to identify stakeholders of this policy and changes in policy tools in developed economies. The outcomes of the research are confronted with the status and possibilities of regional policy application for the creative economy in chosen regions in the Slovak economy. On the basis of this confrontation the authors propose changes in the applied policy approach. The authors also deal with broader context, oriented on the definition of the regional policy, conceptual approaches, as well as some specific forms for the regulation of conditions for the creative activities development in the specific regional environment. The structure of the paper about the supporting policy for the creative economy development in the regions of the Slovak Republic is divided into two parts. The first part is focused on theoretical approaches toward regional policy and possibilities of its application in the support of the creative economy mainly from the view of tasks and status of institutions able to influence this development process. The authors use the knowledge of institutional economy, namely functions and types of institutions, possibilities of policy tools usage and possibilities of institutions' activation at various levels (local, regional, national, international, perhaps internal and external institutions). The second part synthesises findings from chosen countries and concentrates on possibilities of the supporting policy application (mainly by institutions) for creation of the conditions for the creative economy development in the specific regional conditions. Possibilities of using the regional policy tools for the support of chosen creative industries are also presented here. In the final part the authors formulate certain generalizations oriented on the creative economy support in regional context.
Keywords: 330